Pengaruh Marketing Mix Terhadap Keputusan Pembelian Pada CV. Justiti Motor Lembata - Barcelona, Oktavianus; Tumbel, Tinneke M.; Kalangi, John A. F (Sam Ratulangi University, 2019)
Related research to study the large influence of mixed mixtures on purchasing decisions on CV. Justitia Lembata Motor can compete from several of the same companies in motorcycle sales. Partially significant for purchasing decisions. Marketing mix is a combination of four variables or activities which are the core of the marketing system, namely: products, price structures, promotional activities, and distribution systems. Consumer purchasing decisions are the final purchases of consumers both individuals and households, who buy goods and services for personal purchases. This research uses quantitative methods, data collection techniques using questionnaires. The population in this study were motorcycle buyers and customers at CV. Justin Motor Lembata. The sample taken was 50 respondents using simple random sampling technique. The research method used is simple linear regression. The 0.014 constant is the same as the result of the buyer's decision to buy at 0.014% and the regression coefficient of the marketing mix variable is 0.667 units to one so that the purchasing decision increases by 0.667%.